Revised CCAFS Theory Of Change Facilitation Guide - Schuetz, Tonya; Förch, Wiebke; Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
﻿This is an updated version of the “CCAFS Theory of Change facilitation guide”. Revised Version: 15 December 2014. This improved, simplified facilitation guide documents the ways CCAFS is currently using an IP approach in its program planning.